Improving the Quality of Halal Tourism through Waqf: Learnings from Existing Literature - Yusuf, Muhammad Zulfikar; Yusuf, Muhammad; Mandalia, Siska (Journal of Mandalika Review, 2025)
Introduction:Despite the growing importance of halal tourism and the potential of waqf as a financing mechanism, there is a lack of comprehensive analysis integrating waqf to enhance halal tourism quality. This study aims to fill this gap by identifying and highlighting models from existing literature that leverage waqf to improve halal tourism offerings, focusing on infrastructure development and service quality enhancement.Methodology: This qualitative research utilizes a literature review approach, analyzing scholarly documents, journals, books, and official reports to highlight various waqf models applicable to halal tourism development. This research involves descriptive and interpretative analysis of the gathered information from these sources.Findings: The study identifies three key waqf models with the potential to improve halal tourism: land substitution (ruislag), cash waqf, and Cash Waqf Linked Sukuk (CWLS). These models can address funding challenges in developing halal tourism infrastructure and enhancing service quality. Of these models, cash waqf has the most significant potential to increase halal tourism. However, implementation faces obstacles such as inefficient asset management, low public awareness, and the need for improved governance structures. Waqf presents a promising avenue for financing and enhancing halal tourism, but realizing its full potential requires addressing management inefficiencies, increasing stakeholder awareness, and fostering collaboration between government bodies, waqf institutions, and private investors.Conclusion: Implementing strategic reforms and leveraging digital solutions can optimize waqf's impact on halal tourism development, contributing to sustainable economic growth and community welfare.